Seed filling in near-isogenic lines of wheat with presence and absence of the stay-green trait - Silva, Simone Alves; Carvalho, Fernando Irajá Felix de; Nedel, Jorge Luis; Cruz, Pedro Jacinto; Peske, Silmar Teichert; Simioni, Daniel; Cargnin, Adeliano (Pesquisa Agropecuaria Brasileira, 2003)
The stay-green trait has been used as an alternative to reduce the senescence in wheat, resulting in an effective functional increase of the leaf area, and an increase in the rate and duration of the seed filling period. The objective of this work was to analyse the rate of dry matter accumulation and the duration of the seed filling period of near-isogenic lines of wheat differentiated by the presence and absence of the stay-green trait. The experiment was conducted in the Experimental Center of Palma, in Pelotas, State of Rio Grande do Sul, in Brazil. Four near-isogenic lines were used: F6-SG and F6-SZ in the year of 2000 and F7-SG and F7-SZ in the year 2001, with five replications. The stay-green trait allowed a higher deposition of plant reserves in the seed, during the phase close to the point of physiological maturity. The duration of the seed filling period in the evaluated genotypes was associated to the dry matter accumulation in the seed. Promoting a larger weight is a trait responsible for the selection of genotypes with high rates of seed filling.